Attitudes and behaviours of marine recreationists towards conservation and environmental protection: A case study of Tel Aviv, Israel. (December 2020) - Portman, Michelle E.; Zhulpa Camporesi, Andre
Abstract: The association between participation in outdoor recreational activities and environmental perceptions and behaviors has been investigated in previous studies, including by conservation scholars. However, few of these have focused specifically on the relationship between participation in marine recreational sports and attitudes and perceptions towards marine conservation. Understanding this relationship is particularly important because although considered the public domain, the marine environment is generally challenging to access and ocean health is under significant threat. This public perception study investigates whether environmental behaviour, interest in and knowledge of marine conservation issues is associated with marine sport activities, particularly, engagement in surfing and SCUBA diving. Researchers administered a survey to recreationalists in and around the beaches of Tel Aviv, Israel. Based on statistical analysis of 170 responses, the study rejects the hypothesis that those who practice these sports are more environmentally aware. Generally, the responses of those who practice surfing on a regular or frequent level indicate lower levels of environmental behaviors and interest in ocean topics, but somewhat higher levels of knowledge about the marine environment. Most of the associations identified from among the responses of SCUBA divers were not statistically significant, which results also from less responses received from those who practice the sport. In any case these findings can be used in the future for designing ocean, coastal and general environmental protection campaigns targeting participants of these and other sports whose participants are dependent on ocean and coasts. Highlights: The study investigates marine sports participants' behaviors and perceptions. The participants of two marine sports surveyed: surfing and SCUBA diving. Respondents answered about environmental behaviors, and interest and knowledge. Participants are not more aware, or interested in marine conservation. Marine sportspersons should be targeted for marine conservation awareness campaigns.